2016
DOI: 10.4012/dmj.2016-137
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-gallate increased the push out bond strength of an epoxy resin sealer to root dentin

Abstract: This study aimed to investigate the effect of epigallocatechin-3-gallate (EGCG) from green tea extract on the push out bond strength of an epoxy resin sealer to root dentin. Seventy single root canal premolars were decoronated and instrumented. The roots were randomly irrigated with different final irrigation protocols (n=16): 17%EDTA (EDTA), 17%EDTA followed by 2.5%NaOCl (EDTA+NaOCl), 17%EDTA followed by 1 mg/mL EGCG (EDTA+EGCG) and 1 mg/mL EGCG (EGCG). Other six root canals were received only 2.5%NaOCl as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 34 publications
0
20
1
1
Order By: Relevance
“…Hence, the probable reason for the highest bond strength with 17% EDTA + green tea could be collagen stabilization and chelating ability by EGCG. [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the probable reason for the highest bond strength with 17% EDTA + green tea could be collagen stabilization and chelating ability by EGCG. [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, by being resin free, they are capable of flowing into the dentinal tubules with no shrinkage. [ 15 16 ] It provides excellent adhesion to dentin and gutta-percha and its ability to seal auxiliary canals, owing to its high flowability and hydrophilic behavior, allows continuous sealing in the presence of moisture. [ 21 ] The interaction of this with tissue fluids results in the formation of mineral tags.…”
Section: Discussionmentioning
confidence: 99%
“…The authors demonstrated that using an ECGC solution at 400 µg/mL for 1 min as the final irrigation in intraradicular dentin, treated with sodium hypochlorite, increased the push-out strength and bond stability of fiber post for a self-etching and an etch-and-rinse adhesive system [35]. Accordingly, in the study of Pheenithicharoenkul et al [36], the use of a 1 mg/mL ECGC solution (for 10 min) or ethylenediaminetetraacetic acid (EDTA) at 17% w/v (for 5 min), followed by ECGC (for 5 min) as the final canal irrigation, demonstrated a higher bond strength than the use of EDTA alone or EDTA with sodium hypochlorite without ECGC in the final canal irrigation solution.…”
Section: Dentin Modifier Dentin Pretreatment Collagen Cross-linkingmentioning
confidence: 98%
“…In recent years, several strategies have been tested in vitro. [12][13][14] The host-derived matrix metalloproteinases are one of the factors leading to this degradation in dentin. 13 Caffeic acid phenethyl ester (CAPE) is an active derivative of propolis, which is a potent antioxidant, and its mechanism is based Iİ˙ on the inhibition of metalloproteinases.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] The host-derived matrix metalloproteinases are one of the factors leading to this degradation in dentin. 13 Caffeic acid phenethyl ester (CAPE) is an active derivative of propolis, which is a potent antioxidant, and its mechanism is based Iİ˙ on the inhibition of metalloproteinases. 15 A study on dentin has shown that CAPE can be used as an antioxidant before the restorative procedure.…”
Section: Introductionmentioning
confidence: 99%